ADSORPSI NITRAT DALAM AIR TAWAR DAN AIR LAUT SINTETIK MENGGUNAKAN ZEOLIT ALAM TERLAPIS OKSIDA BESI - , Kuntari; , Dr. Nurul Hidayat Aprilita, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A research on adsorption of NO3- using iron oxide coated natural zeolite has been conducted. This research aimed to examine the ability of iron oxide coated natural zeolite in NO3- adsorpstion. Some adsorption parameters i.e. adsorbent mass, initial pH, adsorption medium, adsorption kinetic and adsorption isotherm were examined in the adsorption processes. The characterization of iron oxide coated natural zeolite was analyzed using X-Ray Diffraction (XRD) method, Infra Red (IR) spectrophotometry and Gas Sorption Analyzer (GSA). The concentration of NO3- was measured quantitatively by sodium salicilate method. The results showed that iron oxide coated on natural zeolite contribute to an increase in the spesific surface area. The specific surface area of adsorbent increased from 26.53 m2/g to 38.87 m2/g. The optimum pH of NO3- adsorption using iron oxide coated natural zeolite was 6.65. Nitrate adsorption in freshwater was best described by pseudo first order kinetic model with k1 value of 4.90x10-3 /min, whereas NO3- adsorption in saltwater was pseudo second order kinetic model with k2 value of 1.8x10-2 g/mg min. The adsorption capacity and average adsorption energy were estimated from Dubinin-Radushkevich isotherm model. The adsorption capacity of iron oxide coated natural zeolite in freshwater and saltwater were 1.05x10-1 mmol/g and 9.70x10-2 mmol/g, respectively. The average adsorption energy in freshwater and saltwater were 1.89 kJ/mol and 1.76 kJ/mol, respectively. The results indicated that NO3- adsorption using natural zeolite coated iron oxide was dominated by physisorption.